REE characteristics of Antarctic eucrites - Shimizu, Hiroshi; Masuda, Akimasa (1982)
P(論文) Rare-earth elements (REE), Ba, Sr and Rb abundances were precisely determined for three Antarctic eucrites (ALH-78132,Y-790260 and Y-790266), Y-7308 howardite, Y-790143 LL chondrite, Pasamonte eucrite, and plagioclase and clinopyroxene fractions of the Y-790266 eucrite. A positive Ce anomaly and Yb-Lu deviation from smoothness characterize REE patterns of Antarctic eucrites. These REE features are commonly observed for Antarctic eucrites which have been analyzed thus far by us and our colleagues, employing mass-spectrometric isotope dilution method. The degrees of Ce and Yb-Lu deviations are small or substantially absent for almost all of non-Antarctic eucrites and Antarctic meteorites other than eucrites. Some discussions are given to the possible implications of the Ce anomaly and Yb-Lu deviation observed in Antarctic eucrites. departmental bulletin paper